Improving Student Learning Outcomes Using the STAD Type Cooperative Model - Sejahtra, Sejahtra; Manalu, Rizki Bastanta B. (Universitas Majalengka, 2024)
The research aims to determine the completeness of learning outcomes and improve student learning outcomes using the STAD Type Cooperative Model in the Physical Education subject, Material Types of Injuries and How to Manage Them in Class IV of State Elementary School 040474 Bunga Baru, Tigabinanga District, Karo Regency T.P. 2023/2024 The research was carried out at SD Negeri 040474 Bunga Baru, Tigabinanga District, with the research subjects being 24 class IV students. The research object is to use the STAD Type Cooperative Model in Physical Education subjects in class IV of SD Negeri 040474 Bunga Baru, Tigabinanga District, Karo Regency T.P. 2023/2024 The data collection tool used was a learning outcomes test. The data analysis technique uses descriptive statistics by comparing the average values of Cycle I and Cycle II. The analysis results in cycle I showed that 18 students completed (75%) and 6 students (25%) did not complete, with an average score of 70.41. The analysis results in cycle II showed that 21 students completed (87.5%) and 3 students did not complete (12.5%), with an average score of 75.41. Based on the results of data analysis, it was concluded that the use of the STAD Type Cooperative Model in Physical Education learning with material on Types of Injuries and How to Treat Them in class IV of SD Negeri 040474 Bunga Baru, Tigabinanga District, Karo Regency T.P. 2023/2024 completed classically and learning outcomes increased.